2013
DOI: 10.1038/nrneph.2013.272
|View full text |Cite|
|
Sign up to set email alerts
|

The gut–renal axis: do incretin-based agents confer renoprotection in diabetes?

Abstract: Diabetic nephropathy is the leading cause of end-stage renal disease worldwide, and is associated with a high risk of cardiovascular morbidity and mortality. Intensive control of glucose levels and blood pressure is currently the mainstay of both prevention and treatment of diabetic nephropathy. However, this strategy cannot fully prevent the development and progression of diabetic nephropathy, and an unmet need remains for additional novel therapies. The incretin-based agents--agonists of glucagon-like peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
85
1
7

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(99 citation statements)
references
References 178 publications
1
85
1
7
Order By: Relevance
“…In addition, DPP-4 has been elucidated to degrade many peptides such as glucagon-like peptide-2 (GLP-2), BNP, ANP, stromal cell-derived factor (SDF)-1α, substance P, neuropeptide Y, peptide YY, and so on. Activation and prolongation of their physiological activities by DPP-4 inhibition can lead to actions such as natriuresis, improvement of inflammation, suppression of the sympathetic nervous activity, suppression of the renin-angiotensin system, vasodilatation, and cytoprotection [33,34]. Natriuresis has been reported to occur by DPP-4 inhibitor independent of GLP-1 receptor [24] because DPP-4 inhibitors have directly reduced the expression of sodium-proton exchanger 3 (NHE3) protein [35], and promoted a distal tubular natriuresis through SDF-1α [36].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, DPP-4 has been elucidated to degrade many peptides such as glucagon-like peptide-2 (GLP-2), BNP, ANP, stromal cell-derived factor (SDF)-1α, substance P, neuropeptide Y, peptide YY, and so on. Activation and prolongation of their physiological activities by DPP-4 inhibition can lead to actions such as natriuresis, improvement of inflammation, suppression of the sympathetic nervous activity, suppression of the renin-angiotensin system, vasodilatation, and cytoprotection [33,34]. Natriuresis has been reported to occur by DPP-4 inhibitor independent of GLP-1 receptor [24] because DPP-4 inhibitors have directly reduced the expression of sodium-proton exchanger 3 (NHE3) protein [35], and promoted a distal tubular natriuresis through SDF-1α [36].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports suggest that DPP-4 inhibitors have antiinflammatory effects and can improve bone marrow function [45,46]. The possibility of scission protection by DPP-4 with antiinflammatory agents such as BNP/ANP (brain natriuretic peptide/atrial natriuretic peptide) or NPY (neuropeptide), which are substrates of DPP-4, is suggested, and an intracorporeal inflammation condition is therefore thought to be ameliorated by DPP-4 inhibitor [47][48][49][50]. This may explain the improved iron bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…Определена эффективность и безопасность этих средств для лиц с нормальной функцией почек [17]. Применение препаратов инкретинового ряда при нарушении функции почек зависит от стадии ХБП [18]. В табли-це представлены рекомендации по назначению пре-паратов инкретинового ряда в зависимости от СКФ.…”
unclassified